VD_FINDINFO HC / 2012 / 601 vom 4. September 2012 - VD Tribunal cantonal (2012)
INVENTAIRE, DROIT DES SUCCESSIONS, SCELLÉS | 552 CC, 553 CC, 319 CPC (CH), 319 let. a CPC (CH), 104 CDPJ, 109 al. 3 CDPJ, 117 CDPJ, 118 CDPJ, 119 CDPJ